Characteristics and Behavioral Patterns of Academic Dishonesty Among High School Students - Galang Putra Ardhipati; Gian Sugiana Sugara; Agung Nugraha; Sunanih (POTENSI : Journal of Education and Human Development, 2025)
This research was motivated by the increasing incidence of cheating behavior among students, particularly at State Senior High School at Tasikmalaya City, which reflects a low awareness of academic integrity. Cheating behavior can be influenced by various factors, such as academic pressure, peer influence, low self-confidence, weak supervision, and a lack of ethical reinforcement within the school environment. The purpose of this study was to provide a general description of students’ cheating behavior in terms of rationalization, pressure, and opportunity.This study employed a descriptive quantitative method using a questionnaire as the data collection instrument. The results showed that most students at Tasikmalaya City demonstrated a moderate level of cheating behavior. Students in the moderate category tended to rationalize their actions as a response to academic pressure, while those in the high category exhibited openness to cheating opportunities without considering ethical aspects. On the other hand, students in the low category demonstrated awareness of the importance of academic honesty. A total of 333 students participated in this study. The findings are expected to serve as a reference for schools—especially for guidance and counseling services—in designing preventive and intervention strategies to address cheating behavior that threatens academic integrity and educational quality